Construção enunciativa e gêneros textuais em propostas de produção textual em material didático de PBE - Gomes, Mirian Frazão (2011)
This study focuses on proposals for textual productions in Brazilian Portuguese for Foreigners didact material, says the construction of utterances and the genres intended for the activities. To do so, it bases on concepts of the Semiolinguistic Theory proposed by Patrick Charaudeau, as discourse organization modes. Sections of activities called Desafio: tarefa comunicativa from the teaching material Terra Brasil: curso de língua e cultura constitute the research data. In the analysis, it was found the predominant mode of enunciation in the construction of a diversified approach and proposals in relation to genres. The survey showed that the proposals lead to many productions in the descriptive discourse organization mode and an apprehension of different genres.